A review on research and development of passive building in China. (October 2021) - Lin, Yaolin; Zhao, Luqi; Yang, Wei; Hao, Xiaoli; Li, Chun-Qing
Abstract: Passive building technology belongs to the near-zero-energy building technology system, which maximizes the utilization of free energy from the ambient environment to reduce building energy consumption. In recent years, it has been widely recognized and developed rapidly. This paper takes a lot of effort to review the advances in the research and development of passive buildings in China, including the development status, representative projects and emerging technologies, design tools, benefit analysis and applied research in various climate zones. It also examines the policies and barriers for the development of passive buildings in China, including local incentive mechanisms, laws and regulations, etc. Finally, the application prospects of passive buildings in China are analyzed and recommendations are made for future development. Highlights: Research and development of passive building in China is comprehensively reviewed. Development status, representative projects, emerging technologies, design tools, benefit analysis are thoroughly examined. Policies and barriers for the development of passive buildings in China are examined. Application prospects in China are analyzed and recommendations are made for future development.